Percutaneous Mechanical Circulation Support Combined with Extracorporeal Membrane Oxygenation (oxyRVAD) in Secondary Right Heart Failure. Issue 4 (July 2018) - Lepper, Philipp M.; Hörsch, Sabrina I.; Seiler, Frederik; Kamp, Annegret; Becker, Sören L.; Lensch, Christian; Conzelmann, Lars O.; Haake, Hendrik; Muellenbach, Ralf M.; Bals, Robert; Kredel, Markus; Langer, Frank; et al.
Abstract : Right heart failure (RHF) because of pulmonary hypertension (PH) is a frequently encountered clinical problem with high mortality. The last resort, if pharmacological therapy fails, is mechanical circulatory support. There is a lack of percutaneous systems to support the right ventricle (RV). Venoarterial extracorporeal membrane oxygenation is widely used as a bailout in acute RHF in non-left ventricular assist device patients. Venoarterial extracorporeal membrane oxygenation does not unload the left ventricle and may cause failure of the left ventricle if used for a longer period of time. We report the long-term use of an ECMO-based percutaneous right ventricular assist system (oxyRVAD) capable to deliver up to 6 L/min of blood flow with a returning cannula placed in the main pulmonary artery used in RHF originating from PH with poor oxygenation. We present a series of four patients on oxyRVAD (mean treatment duration 15 ± 7.6 days). Patients benefited from the system clinically; however, two patients eventually died while on oxyRVAD. Nevertheless, we provide a proof-of-concept of this system in PH patients, which is feasible and might provide a useful "bridge-to-recovery" or "bridge-to-transplant" option in the management of patients with severe RHF because of PH.